KH. R. Ansnawi’s Thoughts on Nationalism Values against Colonialism and Imperialism - Ozi Setiadi; Zakaria Husin Lubis (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2022)
PurposeThe research aimed to explore KH.R. Asnawi’s thoughts as one of Nahdlatul Ulama founders, on nationalism and patriotism values against colonialism and imperialism in Indonesia. MethodsThis qualitative study applied a historical research design relying on KH. R. Asnawi’s works as the primary data source. The secondary data sources included books and journals discussing KH.R. Asnawi’s thoughts of nationalism and patriotism values. The research also implemented Focus Group Discussion to understand his thoughts comprehensively. The data collected was then analyzed qualitatively using historical and political approaches Results/FindingThe study found that KH. R Asnawi’s thoughts of nationalism was fiqh centric that he was a religious nationalist figure. While the statesmanship values contained in his works included unity, justice, love for the homeland, and divine values. ConclusionThe study concluded that KH. R. Asnawi’s thoughts of nationalism and statesmanship values belongs to the integrism type influenced by theology, fiqh and pesantren education.